2017
DOI: 10.3390/nu9121341
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prebiotic Blend Product Prevents Irritable Bowel Syndrome in Mice by Improving Gut Microbiota and Modulating Immune Response

Abstract: Irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder yet it still lacks effective prevention therapies. The aim of this study is to determine whether a novel prebiotic blend (PB) composed of fructo-oligosaccharide (FOS), galactooligosaccharide (GOS), inulin and anthocyanins could be effective in preventing the development of IBS. We explored the possible mechanisms both in animal and in cells. Post-infectious IBS models in C57BL/6 mice were established and were pretreated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 83 publications
0
54
0
Order By: Relevance
“…A recent study in vivo tested a blended prebiotic, which contains FOS, GOS, inulin and anthocyanidin (a class of polyphenols), on mice, and it showed an anti-inflammatory power on Caco-2 cells and in IBS symptoms by modulating microbiota. These results show that the synergistic action of more than one prebiotic could perhaps have greater effects on gastrointestinal symptoms [129]. A recent meta-analysis that evaluated the effects of FOS and GOS on IBS symptoms showed that both types of prebiotics did not have important effects on symptoms except for GOS that provided a significant effect on global IBS symptoms but not on abdominal pain [130] Moreover, psyllium is usually used in chronic constipation due to its capability to retain water in the small intestine, tinning the stool and increasing the defecation frequency [111].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 76%
“…A recent study in vivo tested a blended prebiotic, which contains FOS, GOS, inulin and anthocyanidin (a class of polyphenols), on mice, and it showed an anti-inflammatory power on Caco-2 cells and in IBS symptoms by modulating microbiota. These results show that the synergistic action of more than one prebiotic could perhaps have greater effects on gastrointestinal symptoms [129]. A recent meta-analysis that evaluated the effects of FOS and GOS on IBS symptoms showed that both types of prebiotics did not have important effects on symptoms except for GOS that provided a significant effect on global IBS symptoms but not on abdominal pain [130] Moreover, psyllium is usually used in chronic constipation due to its capability to retain water in the small intestine, tinning the stool and increasing the defecation frequency [111].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 76%
“…In fact, some gut bacteria have been found with capacities of regulating PPARs. For example, mice artificially infected with Trichinella spiralis could induce a decrease in the levels of PPARγ in the colon, which is accompanied by a decline in beneficial species (such as Akkermansia ) and increase in pathogenic bacteria (such as Escherichia / Shigella ) (Chen et al 2017). Another pathway of importance that was differentially decreased in the obese adolescent was adipocytokine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Human nutrition and health are intrinsically related with the efficiency of the gastrointestinal system. Through the active modulation of the colonic microbiota with a regular daily ingestion of prebiotics, such as fructo-oligosaccharides (FOS), it has been possible to reduce a great number of pathophysiological disorders and associated chronic diseases such as irritable bowel syndrome (Chen et al, 2017), osteoporosis (Bryk et al, 2015), obesity (Whelan, Efthymiou, Judd, Preedy, & Taylor, 2006), metabolic syndrome and dyslipidaemia (Mallappa et al, 2012), immune system regulation (Frei, Akdis, & O'Mahony, 2015) and colon cancer (Pool-Zobel, 2005). FOS have been extensively used as prebiotics in diabetic, dietetic and infant foods (Al-Sheraji et al, 2013;Padma & Prabhasankar, 2014;Panesar, Kumari, & Panesar, 2013).…”
Section: Introductionmentioning
confidence: 99%